1985
DOI: 10.1038/sc.1985.8
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin disposition kinetics in humans with spinal cord injury

Abstract: SummaryThe disposition kinetics of gentamicin, an aminoglycoside antibiotic, were studied in seven tetraplegic and six paraplegic volunteers. The volume of distribution of gentamicin in 1/ kg of body weight varied in a statistically significant way from values of this parameter measured in normal subjects. The elimination of gentamicin in spinal man proceeded in a log-linear fashion accurately characterized by a one compartment open-model with a half-life of approximately 2 hours.The clinical significance of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 11 publications
2
32
1
Order By: Relevance
“…The present results, as well as those reported elsewhere by our group 4,[12][13][14][15] and other researchers, [5][6][7][8][9][10] clearly indicate that pharmacokinetics of a given drug can exhibit important differences in patients with SCI compared with able-bodied individuals. An adequate understanding of these phenomena is warranted, and therefore further research is still required.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present results, as well as those reported elsewhere by our group 4,[12][13][14][15] and other researchers, [5][6][7][8][9][10] clearly indicate that pharmacokinetics of a given drug can exhibit important differences in patients with SCI compared with able-bodied individuals. An adequate understanding of these phenomena is warranted, and therefore further research is still required.…”
Section: Discussionsupporting
confidence: 79%
“…Significant changes in volume of distribution and clearance have been reported in patients after cord lesion for various drugs, including aminoglycosides 5 and methylprednisolone. 6 Likewise, SCI-induced changes in oral drug absorption have been reported for paracetamol, 4,7 dantrolene 8 and theophylline, 9 and it has been suggested that these changes could have an impact on the efficacy and safety of a variety of drugs in this population. 10 Characterization of the pathophysiological alterations underlying pharmacokinetic changes that occur in patients with SCI has been complicated because of the important variability induced by differences in injury characteristics, as well as in the individual conditions of each patient.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs present an increased bioavailability due to impaired hepatic metabolic clearance. 30,43,49 Experimental studies have shown that increasing hepatic microvascular blood flow through nitric oxide-mediated vasodilation using L-arginine, a nitric oxide precursor, could ameliorate PK alterations at this level. 50 …”
Section: Altered Pkmentioning
confidence: 99%
“…A reduced delivery of antibiotics into paralyzed areas could contribute as well because of changes that can be detected within 1 week of spinal cord injury, including the following: (i) elevation of interstitial tissue pressure and decreased blood flow (16); (ii) increase in extracellular volume of distribution caused by erosion of muscle mass and decreased venomotor tone (15); (iii) protein catabolism in peripheral tissues (4,7,12).…”
Section: Discussionmentioning
confidence: 99%